Poly(2-ethyl-2-oxazoline)–PLA-g–PEI amphiphilic triblock micelles for co-delivery of minicircle DNA and chemotherapeutics - Gaspar, Vítor Manuel Abreu (2018)
Submitted by Ilídio Correia (icorreia@ubi.pt) on 2018-03-20T11:16:18Z No. of bitstreams: 1 2014 Gaspar JCR.pdf: 5581015 bytes, checksum: 1dcbdf679f906cdb89d67f760d310a40 (MD5)